Two Contrasting Demographic Processes Shape the Divergence and Evolution of the Widespread Arid Zone Specialist, Petrogale lateralis - Sally Potter; Craig Moritz; Kym Ottewell; Emily Roycroft; Anna J. MacDonald; Margaret Byrne; Steven J. B. Cooper; David J. Pearson; Mark D. B. Eldridge (Molecular Ecology, 2026)
Organisms living in arid environments are predicted to be at increased risk of extinction under climatic and anthropogenic change. Response to past climate change can provide some insights into these risks; however, our understanding of the diversification and evolutionary history of many arid‐adapted species is still limited, particularly in Australia. Here, we evaluate the demographic and evolutionary history of a widespread Australian marsupial, the black‐footed rock‐wallaby ( Petrogale lateralis ), with a highly fragmented contemporary distribution across Australia's arid biome and offshore islands. Combining genomic data from historical and modern samples, we evaluate the divergence history of the five P. lateralis subspecies. Our results show that the species has experienced a Pleistocene‐age demographic expansion across the Australian arid biome, with subsequent geographic fragmentation of populations and subspecies. We find negligible gene flow between most extant populations/subspecies, yet low divergence between populations of P. l. lateralis and currently recognised subspecies. Individuals on islands have extremely low genetic diversity and high inbreeding coefficients, in contrast to naturally fragmented mainland populations, suggesting a stronger bottleneck experienced on islands. Our results indicate connectivity of populations within the past ~160–640 kya despite their current disjunct distributions, providing important context for conservation management and potential genetic rescue. However, given the large ecological gradient and chromosomal variation within this species, assessment of ecological differences and risks of outbreeding depression will be important before decisions to mix across geographically distant populations and/or subspecies. This study demonstrates how museum genomics improves our ability to resolve complex evolutionary histories and guide conservation.

Repeated Independent Formation of Triploid Lineages Contributes to Clonal Diversity in Heteronotia binoei Parthenogens - Kate E. O'Hara; Stephen M. Zozaya; Erin E. Hahn; Clare E. Holleley; Craig Moritz (Molecular Ecology, 2026)
Parthenogenesis, or all‐female clonal reproduction, is rare among vertebrates. This is often attributed to the selective disadvantages of assumed reduction of genetic diversity in the absence of sex. However, parthenogenetic vertebrates have highly complex evolutionary histories, with most arising through hybridisation and many being polyploid. Here, we show that geographically widespread triploid parthenogenetic forms of the Australian gekkonid Heteronotia binoei are considerably diverse despite their clonal reproductive mode, with patterns of variation consistent with two previously identified reciprocal hybrid origins and numerous backcrossing events. We also confirm a two‐fold increase in genome‐wide heterozygosity among parthenogens (10.6%) compared with the sexual progenitors (4.63%). Our SNP‐based diversity estimates exceed prior predictions for clonal H. binoei lineages based on karyotype and allozyme data. We also find evidence of repeated and geographically widespread backcrossing in both western and central Australia. This supports the long‐standing hypothesis that parthenogens are able to partially recover parental niches by ‘freezing’ genotypic diversity present within the sexual forms. Understanding how asexual clones attain ecological success has implications for managing both invasive species, many of which are clonal, and threatened species, which often face similar challenges associated with reduced genetic diversity. Overall, our findings demonstrate that sex, historical or ongoing, is instrumental in the persistence of asexual lineages, contributing to a broader understanding of the evolutionary dynamics of parthenogenesis.

Genetic mixing in conservation translocations increases diversity of a keystone threatened species, Bettongia lesueur - Heidi M. Nistelberger; Emily Roycroft; Anna J. Macdonald; Shelley McArthur; Lauren C. White; Patrick G. S. Grady; Jennifer Pierson; Colleen Sims; Saul Cowen; Katherine Moseby; Katherine Tuft; Craig Moritz; et al. (Molecular Ecology, 2025)
Translocation programmes are increasingly being informed by genetic data to monitor and enhance conservation outcomes for both natural and established populations. These data provide a window into contemporary patterns of genetic diversity, structure and relatedness that can guide managers in how to best source animals for their translocation programmes. The inclusion of historical samples, where possible, strengthens monitoring by allowing assessment of changes in genetic diversity over time and by providing a benchmark for future improvements in diversity via management practices. Here, we used reduced representation sequencing (ddRADseq) data to report on the current genetic health of three remnant and seven translocated boodie ( Bettongia lesueur ) populations, now extinct on the Australian mainland. In addition, we used exon capture data from seven historical mainland specimens and a subset of contemporary samples to compare pre‐decline and current diversity. Both data sets showed the significant impact of population founder source (whether multiple or single) on the genetic diversity of translocated populations. Populations founded by animals from multiple sources showed significantly higher genetic diversity than the natural remnant and single‐source translocation populations, and we show that by mixing the most divergent populations, exon capture heterozygosity was restored to levels close to that observed in pre‐decline mainland samples. Relatedness estimates were surprisingly low across all contemporary populations and there was limited evidence of inbreeding. Our results show that a strategy of genetic mixing has led to successful conservation outcomes for the species in terms of increasing genetic diversity and provides strong rationale for mixing as a management strategy.

Repeated Mitochondrial Capture With Limited Genomic Introgression in a Lizard Group - Wesley J. Read; Rebecca J. Laver; Ching Ching Lau; Craig Moritz; Stephen M. Zozaya (Molecular Ecology, 2025)
Mitochondrial introgression is common among animals and is often first identified through mitonuclear discordance—discrepancies between evolutionary relationships inferred from mitochondrial DNA (mtDNA) and nuclear DNA (nuDNA). Over recent decades, genomic data have also revealed extensive nuclear introgression in many animal groups, with implications for genetic and phenotypic diversity. However, the extent to which mtDNA introgression corresponds to nuDNA introgression varies. Here, we investigated historical and recent introgression in the Gehyra nana ‐occidentalis clade, a complex group of Australian geckos with documented cases of mitonuclear discordance suggestive of repeated mtDNA introgression. We hypothesised that mitonuclear discordance in this clade reflects mtDNA introgression with substantial nuclear introgression. Despite evidence of repeated mtDNA introgression, however, we found little to no evidence of historical nuDNA introgression using exon capture and genome‐wide single nucleotide polymorphism (SNP) data. We also found no evidence of gene flow at modern contact zones and detected only a single early generation hybrid. Unsurprisingly, given these results, we found no evidence of transgressive, intermediate, or more variable morphological phenotypes in taxa with introgressed mtDNA. These findings suggest that hybridisation in this system has, at least in some cases, resulted in repeated mitochondrial introgression with little or no nuclear introgression. This pattern aligns with other studies showing limited nuDNA introgression in taxa with mitonuclear discordance, highlighting a potentially broader trend in animal radiations.

Notes from the taxonomic disaster zone: Evolutionary drivers of intractable species boundaries in an Australian lizard clade (Scincidae: Ctenotus ) - Ivan Prates; Mark N. Hutchinson; Sonal Singhal; Craig Moritz; Daniel L. Rabosky (Molecular Ecology, 2024)
Genomic‐scale datasets, sophisticated analytical techniques, and conceptual advances have disproportionately failed to resolve species boundaries in some groups relative to others. To understand the processes that underlie taxonomic intractability, we dissect the speciation history of an Australian lizard clade that arguably represents a “worst‐case” scenario for species delimitation within vertebrates: the Ctenotus inornatus species group, a clade beset with decoupled genetic and phenotypic breaks, uncertain geographic ranges, and parallelism in purportedly diagnostic morphological characters. We sampled hundreds of localities to generate a genomic perspective on population divergence, structure, and admixture. Our results revealed rampant paraphyly of nominate taxa in the group, with lineages that are either morphologically cryptic or polytypic. Isolation‐by‐distance patterns reflect spatially continuous differentiation among certain pairs of putative species, yet genetic and geographic distances are decoupled in other pairs. Comparisons of mitochondrial and nuclear gene trees, tests of nuclear introgression, and historical demographic modelling identified gene flow between divergent candidate species. Levels of admixture are decoupled from phylogenetic relatedness; gene flow is often higher between sympatric species than between parapatric populations of the same species. Such idiosyncratic patterns of introgression contribute to species boundaries that are fuzzy while also varying in fuzziness. Our results suggest that “taxonomic disaster zones” like the C. inornatus species group result from spatial variation in the porosity of species boundaries and the resulting patterns of genetic and phenotypic variation. This study raises questions about the origin and persistence of hybridizing species and highlights the unique insights provided by taxa that have long eluded straightforward taxonomic categorization.

Dragons in the tropics – Phylogeography and speciation in Diporiphora lizards and common geographic breaks in co-distributed taxa - Jessica Fenker; Jane Melville; Craig Moritz (Molecular Phylogenetics and Evolution, 2024)

Speciation across biomes: Rapid diversification with reproductive isolation in the Australian delicate mice - Emily Roycroft; Fred Ford; Till Ramm; Rhiannon Schembri; William G. Breed; Phoebe A. Burns; Kevin C. Rowe; Craig Moritz (Molecular Ecology, 2024)
Phylogeographic studies of continental clades, especially when combined with palaeoclimate modelling, provide powerful insight into how environment drives speciation across climatic contexts. Australia, a continent characterized by disparate modern biomes and dynamic climate change, provides diverse opportunity to reconstruct the impact of past and present environments on diversification. Here, we use genomic‐scale data (1310 exons and whole mitogenomes from 111 samples) to investigate Pleistocene diversification, cryptic diversity, and secondary contact in the Australian delicate mice (Hydromyini: Pseudomys ), a recent radiation spanning almost all Australian environments. Across northern Australia, we find no evidence for introgression between cryptic lineages within Pseudomys delicatulus sensu lato, with palaeoclimate models supporting contraction and expansion of suitable habitat since the last glacial maximum. Despite multiple contact zones, we also find little evidence of introgression at a continental scale, with the exception of a potential hybrid zone in the mesic biome. In the arid zone, combined insights from genetic data and palaeomodels support a recent expansion in the arid specialist P. hermannsburgensis and contraction in the semi‐arid P. bolami . In the face of repeated secondary contact, differences in sperm morphology and chromosomal rearrangements are potential mechanisms that maintain species boundaries in these recently diverged species. Additionally, we describe the western delicate mouse as a new species and recommend taxonomic reinstatement of the eastern delicate mouse. Overall, we show that speciation in an evolutionarily young and widespread clade has been driven by environmental change, and potentially maintained by divergence in reproductive morphology and chromosome rearrangements.

Initiation of speciation across multiple dimensions in a rock‐restricted, tropical lizard - Stephen M. Zozaya; Luisa C. Teasdale; Leonardo G. Tedeschi; Megan Higgie; Conrad J. Hoskin; Craig Moritz (Molecular Ecology, 2023)
Population isolation and concomitant genetic divergence, resulting in strong phylogeographical structure, is a core aspect of speciation initiation. If and how speciation then proceeds and ultimately completes depends on multiple factors that mediate reproductive isolation, including divergence in genomes, ecology and mating traits. Here we explored these multiple dimensions in two young (Plio‐Pleistocene) species complexes of gekkonid lizards ( Heteronotia ) from the Kimberley–Victoria River regions of tropical Australia. Using mitochondrial DNA screening and exon capture phylogenomics, we show that the rock‐restricted Heteronotia planiceps exhibits exceptional fine‐scale phylogeographical structure compared to the codistributed habitat generalist Heteronotia binoei . This indicates pervasive population isolation and persistence in the rock‐specialist, and thus a high rate of speciation initiation across this geographically complex region, with levels of genomic divergence spanning the “grey zone” of speciation. Proximal lineages of H. planiceps were often separated by different rock substrates, suggesting a potential role for ecological isolation; however, phylogenetic incongruence and historical introgression were inferred between one such pair. Ecomorphological divergence among lineages within both H. planiceps and H. binoei was limited, except that limestone‐restricted lineages of H. planiceps tended to be larger than rock‐generalists. By contrast, among‐lineage divergence in the chemical composition of epidermal pore secretions (putative mating trait) exceeded ecomorphology in both complexes, but with less trait overlap among lineages in H. planiceps . This system—particularly the rock‐specialist H. planiceps— highlights the role of multidimensional divergence during incipient speciation, with divergence in genomes, ecomorphology and chemical signals all at play at very fine spatial scales.

Linking life history to landscape for threatened species conservation in a multiuse region - Robyn E. Shaw; Peter B. Spencer; Lesley A. Gibson; Judy A. Dunlop; Janine E. Kinloch; Karel Mokany; Margaret Byrne; Craig Moritz; Harriet Davie; Kenny J. Travouillon; Kym M. Ottewell (Conservation Biology, 2023)
Landscape‐scale conservation that considers metapopulation dynamics will be essential for preventing declines of species facing multiple threats to their survival. Toward this end, we developed a novel approach that combines occurrence records, spatial–environmental data, and genetic information to model habitat, connectivity, and patterns of genetic structure and link spatial attributes to underlying ecological mechanisms. Using the threatened northern quoll ( Dasyurus hallucatus ) as a case study, we applied this approach to address the need for conservation decision‐making tools that promote resilient metapopulations of this threatened species in the Pilbara, Western Australia, a multiuse landscape that is a hotspot for biodiversity and mining. Habitat and connectivity were predicted by different landscape characteristics. Whereas habitat suitability was overwhelmingly driven by terrain ruggedness, dispersal was facilitated by proximity to watercourses. Although there is limited evidence for major physical barriers in the Pilbara, areas with high silt and clay content (i.e., alluvial and hardpan plains) showed high resistance to dispersal. Climate subtlety shaped distributions and patterns of genetic turnover, suggesting the potential for local adaptation. By understanding these spatial–environmental associations and linking them to life‐history and metapopulation dynamics, we highlight opportunities to provide targeted species management. To support this, we have created habitat, connectivity, and genetic uniqueness maps for conservation decision‐making in the region. These tools have the potential to provide a more holistic approach to conservation in multiuse landscapes globally.

Comparative phylogeography in the genomic age: Opportunities and challenges - Angela McGaughran; Libby Liggins; Katharine A. Marske; Michael N Dawson; Lauren M. Schiebelhut; Shane D. Lavery; L. Lacey Knowles; Craig Moritz; Cynthia Riginos (Journal of Biogeography, 2022)
Aim We consider the opportunities and challenges comparative phylogeography (CP) faces in the genomic age to determine: (1) how we can maximise the potential of big CP analyses to advance biogeographic and macroevolutionary theory; and (2) what we can, and will struggle, to achieve using CP approaches in this era of genomics. Location World‐wide. Taxon All. Methods We review the literature to discuss the future of CP ‐ particularly examining CP insights enabled by genomics that may not be possible for single species and/or few molecular markers. We focus on how geography and species' natural histories interact to yield congruent and incongruent patterns of neutral and adaptive processes in the context of both historical and recent rapid evolution. We also consider how CP genomic data are being stored, accessed, and shared. Results With the widespread availability of genomic data, the shift from a single‐ to a multi‐locus perspective is resulting in detailed historical inferences and an improved statistical rigour in phylogeography. However, the time and effort required for collecting co‐distributed species and accruing species‐specific ecological knowledge continue to be limiting factors. Bioinformatic skills and user‐friendly analytical tools, alongside the computational infrastructure required for big data, can also be limiting. Main conclusions Over the last ~35 years, there has been much progress in understanding how intraspecific genetic variation is geographically distributed. The next major steps in CP will be to incorporate evolutionary processes and community perspectives to account for patterns and responses among co‐distributed species and across temporal scales, including those related to anthropogenic change. However, the full potential of CP will only be realised if we employ robust study designs within a sound comparative framework. We advocate that phylogeographers adopt such consistent approaches to enhance future comparisons to present‐day findings.

Population genomics and sexual signals support reproductive character displacement in Uperoleia (Anura: Myobatrachidae) in a contact zone - Frederick R. Jaya; Jessie C. Tanner; Michael R. Whitehead; Paul Doughty; J. Scott Keogh; Craig C. Moritz; Renee A. Catullo (Molecular Ecology, 2022)
When closely related species come into contact via range expansion, both may experience reduced fitness as a result of the interaction. Selection is expected to favour traits that minimize costly interspecies reproductive interactions (such as mismating) via a phenomenon called reproductive character displacement (RCD). Research on RCD frequently assumes secondary contact between species, but the geographical history of species interactions is often unknown. Population genomic data permit tests of geographical hypotheses about species origins and secondary contact through range expansion. We used population genomic data from single nucleotide polymorphisms (SNPs), mitochondrial sequence data, advertisement call data and morphological data to investigate a species complex of toadlets ( Uperoleia borealis, U. crassa, U. inundata ) from northern Australia. Although the three species of frogs were morphologically indistinguishable in our analysis, we determined that U. crassa and U. inundata form a single species (synonymized here) based on an absence of genomic divergence. SNP data identified the phylogeographical origin of U. crassa as the Top End, with subsequent westward invasion into the range of U. borealis in the Kimberley. We identified six F 1 hybrids, all of which had the U. borealis mitochondrial haplotype, suggesting unidirectional hybridization. Consistent with the RCD hypothesis, U. borealis and U. crassa sexual signals differ more in sympatry than in allopatry. Hybrid males have intermediate calls, which probably reduces attractiveness to females. Integrating population genomic data, mitochondrial sequencing, morphology and behavioural approaches provides an unusually detailed collection of evidence for reproductive character displacement following range expansion and secondary contact.

Range-wide genomic scans and tests for selection identify non-neutral spatial patterns of genetic variation in a non-model amphibian species (Pelobates cultripes) - Adam Joseph Doncheff Marques; Jeffrey Owen Hanson; Miguel Camacho-Sanchez; Iñigo Martínez-Solano; Craig Moritz; Pedro Tarroso; Guillermo Velo-Antón; Ana Veríssimo; Sílvia Benoliel Carvalho (Conservation Genetics, 2022)

Environmental resistance and habitat quality influence dispersal of the saltwater crocodile - Yusuke Fukuda; Craig Moritz; Namchul Jang; Grahame Webb; Hamish Campbell; Keith Christian; Garry Lindner; Sam Banks (Molecular Ecology, 2022)
Landscape genetics commonly focuses on the effects of environmental resistance on animal dispersal patterns, but there is an emerging focus on testing environmental effects on emigration and settlement choices. In this study, we used landscape genetics approaches to quantify dispersal patterns in the world's largest crocodilian, the saltwater crocodile ( Crocodylus porosus ), and demonstrated environmental influences on three processes that comprise dispersal: emigration, movement and settlement. We found that both environmental resistance and properties of the source and destination catchments (proportion of breeding habitat) were important factors influencing observed dispersal events. Our habitat quality variables related to hypotheses about resource competition and represented the ratio of breeding habitat (which limits carrying capacity), suggesting that competition for habitat influences emigration and settlement choices, together with the strong effect of environmental resistance to movement (where high‐quality habitat was associated with greatest environmental permeability). Approximately 42% of crocodiles were migrants from populations other than their sampling locations and some outstandingly productive populations had a much higher proportion of emigration rather than immigration. The distance most commonly travelled between source and destination was 150–200 km although a few travelled much longer distances, up to 600–700 km. Given the extensive dispersal range, individual catchments or hydrographic regions that combine two or three adjacent catchments are an appropriate scale for population management.

Climate-Relevant Ocean Transport Measurements in the Atlantic and Arctic Oceans - Barbara Berx; Denis Volkov; Johanna Baehr; Molly Baringer; Peter Brandt; Kristin Burmeister; Stuart Cunningham; Marieke de Jong; Laura de Steur; Shenfu Dong; Eleanor Frajka-Williams; Gustavo Goni; et al. (Oceanography, 2021)

Predictors of phylogeographic structure among codistributed taxa across the complex Australian monsoonal tropics - Jessica Fenker; Leonardo G. Tedeschi; Jane Melville; Craig Moritz (Molecular Ecology, 2021)
Differences in the geographic scale and depth of phylogeographic structure across codistributed taxa can reveal how microevolutionary processes such as population isolation and persistence drive diversification. In turn, environmental heterogeneity, species’ traits, and historical biogeographic barriers may influence the potential for isolation and persistence. Using extensive SNP data and a combination of population genetic summary statistics and landscape genomic analyses, we explored predictors of the scale and depth of phylogeographic structure in codistributed lizard taxa from the topographically and climatically complex monsoonal tropics (AMT) of Australia. We first resolved intraspecific lineages and then tested whether genetic divergence across space within lineages is related to isolation by distance, resistance and/or environment and whether these factors differ across genera or between rock‐related versus habitat generalist taxa. We then tested whether microevolutionary processes within lineages explain differences in the geographic scale and depth of intraspecific phylogeographic lineages. The results indicated that landscape predictors of phylogeographic structure differ between taxa. Within lineages, there was prevalent isolation by distance, but the strength of isolation by distance is independent of the taxonomic family, habitat specialization, and climate. Isolation by environment is the strongest predictor of landscape‐scale genetic divergence for all taxa, with both temperature and precipitation acting as limiting factors. The strength of isolation by distance does not predict the geographic scale of the phylogeographic structure. However, more localized lineages had higher mean individual heterozygosity and less negative Tajima's D. This result implies that finer‐scale phylogeographic structuring within species is associated with larger and more stable populations and, hence, persistence.

Evolutionary history of Neotropical savannas geographically concentrates species, phylogenetic and functional diversity of lizards - Jessica Fenker; Fabricius M. C. B. Domingos; Leonardo G. Tedeschi; Dan F. Rosauer; Fernanda P. Werneck; Guarino R. Colli; Roger M. D. Ledo; Emanuel M. Fonseca; Adrian A. Garda; Derek Tucker; Jack W. Sites; Maria F. Breitman; et al. (Journal of Biogeography, 2020)
Aim Understanding where and why species diversity is geographically concentrated remains a challenge in biogeography and macroevolution. This is true for the Cerrado, the most biodiverse tropical savanna in the world, which has experienced profound biodiversity loss. Previous studies have focused on a single metric (species composition), neglecting the fact that ‘species’ within the biome are often composed of cryptic species. In order to identify biodiversity hotspots more robustly and across multiple dimensions we integrate functional, spatial and new phylogeographic data for the Cerrado lizard fauna by (a) mapping the spatial patterns of species and phylogenetic diversity; and (b) using endemism measures to identify areas of unique diversity. We then quantify the extent to which existing protected areas represent the diversity. Location Brazilian savanna (Cerrado). Methods We generated species distribution models using distribution records for all Cerrado lizard species. These, combined with mitochondrial DNA phylogenies and natural history data, allowed us to map species richness, phylogenetic and functional diversity and phylogenetic and weighted endemism. Phylogenetic endemism maps were then cross‐referenced against protected areas to calculate the amount of evolutionary history preserved within these areas. Results The central region of the Cerrado, a vast and climatically stable plateau, stands out as important under all biodiversity metrics. Including evolutionary relationships in biodiversity assessment, we detected four regional hotspots with high concentration of spatially restricted evolutionary diversity. Protected areas cover only 10% of the Cerrado area and hold 11.64% of the summed phylogenetic endemism of all lizards in the biome. Main Conclusions We highlighted both stable ( Chapada dos Veadeiros and Serra do Espinhaço plateaus) and environmentally heterogenous regions ( Araguaia and Tocantins valleys) as hotspots of evolutionary diversity. The creation and/or manipulation of areas for conservation are essential for the conservation and survival of the rich and endemic lizard fauna of the Cerrado.

Contrasting scales of local persistence between monsoonal and arid biomes in closely related, low‐dispersal vertebrates - Sally Potter; Ana C. Afonso Silva; Jason G. Bragg; Sarah R. Catalano; Stephen Donnellan; Paul Doughty; Mitchell L. Scott; Craig Moritz (Journal of Biogeography, 2019)
Aim Focussing on pairs of sister species across three genera of scincid lizards, we use genomic evidence to test for larger‐scale, late‐Pleistocene changes in distributions of lizards in the Australian arid zone (AZ) than in the adjacent monsoonal tropics (MT). Location Northern and central Australia. Taxon Scincidae: Squamata. Methods We sequenced ~2000 nuclear exons and one mitochondrial gene across the distributions of species with primarily MT or AZ distributions from three genera of lizards. Using phylogenetic analysis and population structure analyses we identified major phylogeographic lineages and then compared the spatial scale of structuring and tested for recent demographic expansions. Results Two genera in particular, Proablepharus and Morethia , showed deeper and more geographically localized phylogeographic diversity in the MT than the AZ. In the MT, localized diversity was prevalent in the relatively mesic regions. By contrast, the AZ was characterized by widespread and often genetically uniform lineages and a higher proportion of these had signals of recent population expansion. Main conclusions Consistent with other recent, but mostly less genetically extensive studies, our results point to deeper and more localized diversity in MT compared to AZ. In turn, this suggests higher local persistence in more mesic and topographically diverse biome through the late Quaternary climate fluctuations. For the AZ, geographically extensive range expansions have likely contributed to the low spatial turnover of this exceptionally rich lizard fauna.

Arctic Mediterranean exchanges: a consistent volume budget and trends in transports from two decades of observations - Svein Østerhus; Rebecca Woodgate; Héðinn Valdimarsson; Bill Turrell; Laura de Steur; Detlef Quadfasel; Steffen M. Olsen; Martin Moritz; Craig M. Lee; Karin Margretha H. Larsen; Steingrímur Jónsson; Clare Johnson; et al. (Ocean Science, 2019)
The Arctic Mediterranean (AM) is the collective name for the Arctic Ocean, the Nordic Seas, and their adjacent shelf seas. Water enters into this region through the Bering Strait (Pacific inflow) and through the passages across the Greenland–Scotland Ridge (Atlantic inflow) and is modified within the AM. The modified waters leave the AM in several flow branches which are grouped into two different categories: (1) overflow of dense water through the deep passages across the Greenland–Scotland Ridge, and (2) outflow of light water – here termed surface outflow – on both sides of Greenland. These exchanges transport heat and salt into and out of the AM and are important for conditions in the AM. They are also part of the global ocean circulation and climate system. Attempts to quantify the transports by various methods have been made for many years, but only recently the observational coverage has become sufficiently complete to allow an integrated assessment of the AM exchanges based solely on observations. In this study, we focus on the transport of water and have collected data on volume transport for as many AM-exchange branches as possible between 1993 and 2015. The total AM import (oceanic inflows plus freshwater) is found to be 9.1 Sv (sverdrup, 1 Sv =106 m3 s−1) with an estimated uncertainty of 0.7 Sv and has the amplitude of the seasonal variation close to 1 Sv and maximum import in October. Roughly one-third of the imported water leaves the AM as surface outflow with the remaining two-thirds leaving as overflow. The overflow water is mainly produced from modified Atlantic inflow and around 70 % of the total Atlantic inflow is converted into overflow, indicating a strong coupling between these two exchanges. The surface outflow is fed from the Pacific inflow and freshwater (runoff and precipitation), but is still approximately two-thirds of modified Atlantic water. For the inflow branches and the two main overflow branches (Denmark Strait and Faroe Bank Channel), systematic monitoring of volume transport has been established since the mid-1990s, and this enables us to estimate trends for the AM exchanges as a whole. At the 95 % confidence level, only the inflow of Pacific water through the Bering Strait showed a statistically significant trend, which was positive. Both the total AM inflow and the combined transport of the two main overflow branches also showed trends consistent with strengthening, but they were not statistically significant. They do suggest, however, that any significant weakening of these flows during the last two decades is unlikely and the overall message is that the AM exchanges remained remarkably stable in the period from the mid-1990s to the mid-2010s. The overflows are the densest source water for the deep limb of the North Atlantic part of the meridional overturning circulation (AMOC), and this conclusion argues that the reported weakening of the AMOC was not due to overflow weakening or reduced overturning in the AM. Although the combined data set has made it possible to establish a consistent budget for the AM exchanges, the observational coverage for some of the branches is limited, which introduces considerable uncertainty. This lack of coverage is especially extreme for the surface outflow through the Denmark Strait, the overflow across the Iceland–Faroe Ridge, and the inflow over the Scottish shelf. We recommend that more effort is put into observing these flows as well as maintaining the monitoring systems established for the other exchange branches.

Current geography masks dynamic history of gene flow during speciation in northern Australian birds - Joshua V. Peñalba; Leo Joseph; Craig Moritz (Molecular Ecology, 2019)
Genome divergence is greatly influenced by gene flow during early stages of speciation. As populations differentiate, geographic barriers can constrain gene flow and so affect the dynamics of divergence and speciation. Current geography, specifically disjunction and continuity of ranges, is often used to predict the historical gene flow during the divergence process. We test this prediction in eight meliphagoid bird species complexes codistributed in four regions. These regions are separated by known biogeographical barriers across northern Australia and Papua New Guinea. We find that bird populations currently separated by terrestrial habitat barriers within Australia and marine barriers between Australia and Papua New Guinea have a range of divergence levels and probability of gene flow not associated with current range connectivity. Instead, geographic distance and historical range connectivity better predict divergence and probability of gene flow. In this dynamic environmental context, we also find support for a nonlinear decrease of the probability of gene flow during the divergence process. The probability of gene flow initially decreases gradually after a certain level of divergence is reached. Its decrease then accelerates until the probability is close to zero. This implies that although geographic connectivity may have more of an effect early in speciation, other factors associated with higher divergence may play a more important role in influencing gene flow midway through and later in speciation. Current geographic connectivity may then mislead inferences regarding potential for gene flow during speciation under a complex and dynamic history of geographic and reproductive isolation.

Biome stability in South America over the last 30 kyr: Inferences from long‐term vegetation dynamics and habitat modelling - Gabriel C. Costa; Arndt Hampe; Marie‐Pierre Ledru; Pablo A. Martinez; Guilherme G. Mazzochini; Donald B. Shepard; Fernanda P. Werneck; Craig Moritz; Ana Carolina Carnaval (Global Ecology and Biogeography, 2018)
Aim The aim was to examine the links between past biome stability, vegetation dynamics and biodiversity patterns. Location South America. Time period Last 30,000 years. Major taxa studied Plants. Methods We classified South America into major biomes according to their dominant plant functional groups (grasses, trees and shrubs) and ran a random forest (RF) classification with data on current climate. We then fitted the algorithm to predict biome distributions for every 1,000 years back to 21,000 yr BP and estimated biome stability by counting how many times a change in climate was predicted to shift a grid cell from one biome to another. We compared our model‐based stability map with empirical estimates from selected pollen records covering the past 30 kyr in terms of vegetation shifts, changes in species composition and time‐lag of vegetation responses. Results We found a strong correlation between our habitat stability map and regional vegetation dynamics. Four scenarios emerged according to the way forest distribution shifted during a climate change. Each scenario related to specific regional features of biome stability and diversity, allowing us to formulate specific predictions on how taxonomic, genetic and functional components of biodiversity might be impacted by modern climate change. Main conclusions Our validated map of biome stability provides important baseline information for studying the impacts of past climate on biodiversity in South America. By focusing exclusively on climatic changes of manifested relevance (i.e., those resulting in significant habitat changes), it provides a novel perspective that complements previous datasets and allows scientists to explore new questions and hypotheses at the local, regional and continental scales.

Pleistocene climatic changes drive diversification across a tropical savanna - Sally Potter; Alexander T. Xue; Jason G. Bragg; Dan F. Rosauer; Emily J. Roycroft; Craig Moritz (Molecular Ecology, 2018)
Spatial responses of species to past climate change depend on both intrinsic traits (climatic niche breadth, dispersal rates) and the scale of climatic fluctuations across the landscape. New capabilities in generating and analysing population genomic data, along with spatial modelling, have unleashed our capacity to infer how past climate changes have shaped populations, and by extension, complex communities. Combining these approaches, we uncover lineage diversity across four codistributed lizards from the Australian Monsoonal Tropics and explore how varying climatic tolerances interact with regional climate history to generate common vs. disparate responses to late Pleistocene change. We find more divergent spatial structuring and temporal demographic responses in the drier Kimberley region compared to the more mesic and consistently suitable Top End. We hypothesize that, in general, the effects of species’ traits on sensitivity to climate fluctuation will be more evident in climatically marginal regions. If true, this points to the need in climatically marginal areas to craft more species‐(or trait)‐specific strategies for persistence under future climate change.

Characterizing divergence through three adjacent Australian avian transition zones - Joshua V. Peñalba; Ian J. Mason; Richard Schodde; Craig Moritz; Leo Joseph (Journal of Biogeography, 2017)
Aim The diversification of the Australian avifauna has been greatly influenced by prominent historical and modern barriers to dispersal. The aims of this study were to characterize the patterns of divergence in population pairs of meliphagoid birds across adjacent transition zones and characterize how well morphometric divergence, habitat association and taxonomic or species ranking can predict genetic divergence. Location Northern Queensland, Australia. Methods Genetic divergence between parental populations on either side of the three biogeographical barriers corresponding to three clusters of hybrid zones was characterized in 27 species complexes of meliphagoid birds using one mitochondrial, 23 autosomal and 12 Z chromosome loci collected from a sequence capture system. Within each species, we characterized morphometric divergence using wing, bill and tail measurements from museum samples. Lastly, we evaluated the predictive power of these morphometric measurements on genetic divergence. Results Population pairs on either side of a transition zone depict a wide range of genomic and morphometric divergence. For some systems, species exhibiting morphometric divergence show little to no genomic divergence, while, conversely, other species exhibiting little to no morphometric divergence may show clear genomic divergence. Species rank is shown to be the strongest predictor for genetic divergence, habitat is the next strongest predictor and morphometric divergence is the weakest predictor. Main conclusions The variation in divergence levels of population pairs affirms that transition zones are ideal natural experiments to study the speciation process. In particular, transition zones allow understanding of how genomic divergence accumulates during speciation. Additionally, standing species rank classifications mostly prove to be robust after genetic characterization. Lastly, the discordance between morphometric and genetic divergence suggests other non‐morphometric phenotypic traits used to designate species rank, such as song or plumage, may play a more important role in predicting genetic divergence.

Range instability leads to cytonuclear discordance in a morphologically cryptic ground squirrel species complex - Mark A. Phuong; Ke Bi; Craig Moritz (Molecular Ecology, 2017)
The processes responsible for cytonuclear discordance frequently remain unclear. Here, we employed an exon capture data set and demographic methods to test hypotheses generated by species distribution models to examine how contrasting histories of range stability vs. fluctuation have caused cytonuclear concordance and discordance in ground squirrel lineages from the Otospermophilus beecheyi species complex. Previous studies in O. beecheyi revealed three morphologically cryptic and highly divergent mitochondrial DNA lineages (named the Northern, Central and Southern lineages based on geography) with only the Northern lineage exhibiting concordant divergence for nuclear genes. Here, we showed that these mt DNA lineages likely formed in allopatry during the Pleistocene, but responded differentially to climatic changes that occurred since the last interglacial (~120,000 years ago). We find that the Northern lineage maintained a stable range throughout this period, correlating with genetic distinctiveness among all genetic markers and low migration rates with the other lineages. In contrast, our results suggested that the Southern lineage expanded from Baja California Sur during the Late Pleistocene to overlap and potentially swamp a contracting Central lineage. High rates of intraspecific gene flow between Southern lineage individuals among expansion origin and expansion edge populations largely eroded Central ancestry from autosomal markers. However, male‐biased dispersal in this system preserved signals of this past hybridization and introgression event in matrilineal‐biased X‐chromosome and mt DNA markers. Our results highlight the importance of range stability in maintaining the persistence of phylogeographic lineages, whereas unstable range dynamics can increase the tendency for lineages to merge upon secondary contact.

Tropical specialist vs. climate generalist: Diversification and demographic history of sister species of Carlia skinks from northwestern Australia - Ana C. Afonso Silva; Jason G. Bragg; Sally Potter; Carlos Fernandes; Maria Manuela Coelho; Craig Moritz (Molecular Ecology, 2017)
Species endemic to the tropical regions are expected to be vulnerable to future climate change due in part to their relatively narrow climatic niches. In addition, these species are more likely to have responded strongly to past climatic change, and this can be explored through phylogeographic analyses. To test the hypothesis that tropical specialists are more sensitive to climate change than climate generalists, we generated and analyse sequence data from mt DNA and ~2500 exons to compare scales of historical persistence and population fluctuation in two sister species of Australian rainbow skinks: the tropical specialist Carlia johnstonei and the climate generalist C. triacantha . We expect the tropical specialist species to have deeper and finer‐scale phylogeographic structure and stronger demographic fluctuations relative to the closely related climate generalist species, which should have had more stable populations through periods of harsh climate in the late Quaternary. Within C. johnstonei , we find that some populations from the northern Kimberley islands are highly divergent from mainland populations. In C. triacantha , one major clade occurs across the deserts and into the mesic Top End, and another occurs primarily in the Kimberley with scattered records eastwards. Where their ranges overlap in the Kimberley, both mitochondrial DNA and nuclear DNA suggest stronger phylogeographic structure and range expansion within the tropical specialist, whereas the climate generalist has minimal structuring and no evidence of recent past range expansion. These results are consistent with the hypothesis that tropical specialists are more sensitive to past climatic change.

Putting indigenous conservation policy into practice delivers biodiversity and cultural benefits - Emilie Ens; Mitchell. L. Scott; Yugul Mangi Rangers; Craig Moritz; Rebecca Pirzl (Biodiversity and Conservation, 2016)

Phylogenomics at the tips: inferring lineages and their demographic history in a tropical lizard, Carlia amax - Sally Potter; Jason G. Bragg; Benjamin M. Peter; Ke Bi; Craig Moritz (Molecular Ecology, 2016)
High‐throughput sequencing approaches offer opportunities to better understand the evolutionary processes driving diversification, particularly in nonmodel organisms. In particular, the 100–1000's of loci that can now be sequenced are providing unprecedented power in population, speciation and phylogenetic studies. Here, we apply an exon capture approach to generate >99% complete sequence and SNP data across >2000 loci from a tropical skink, Carlia amax , and exploit these data to identify divergent lineages and infer their relationships and demographic histories. This is especially relevant to low‐dispersal tropical taxa that often have cryptic diversity and spatially dynamic histories. For C. amax , clustering of nuclear SNP s and coalescent‐based species delimitation analyses identify four divergent lineages, one fewer than predicted based on geographically coherent mt DNA clades (>9.4% sequence divergence). Three of these lineages are widespread and parapatric on the mainland, whereas the most divergent is restricted to islands off the northeast Northern Territory. Tests for population expansion reject an equilibrium isolation‐by‐distance model for two of the three widespread lineages and infer refugial expansion sources in the relatively mesic northeast Top End and northwest Kimberley. The latter is already recognized as a hotspot of endemism, but our results also suggest that a stronger focus on the northeast Top End, and adjacent islands is warranted. More generally, our results show how genome‐reduction methods such as exon capture can yield insights into the pattern and dynamics of biodiversity across complex landscapes with as yet poorly understood biogeographic history and how exon data can link between population and phylogenetic questions.

Deep divergence and structure in the Tropical Oceanic Pacific: a multilocus phylogeography of a widespread gekkonid lizard (Squamata: Gekkonidae: Gehyra oceanica ) - Maria A. Tonione; Robert N. Fisher; Catherine Zhu; Craig Moritz (Journal of Biogeography, 2016)
Aim The islands of the Tropical Oceanic Pacific ( TOP ) host both local radiations and widespread, colonizing species. The few phylogeographical analyses of widespread species often point to recent human‐aided expansions through the Pacific, suggesting that the communities are recently assembled. Here we apply multilocus data to infer biogeographical history of the gekkonid lizard, Gehyra oceanica, which is widespread, but for which prior analyses suggested a pre‐human history and in situ diversification. Location Tropical Oceanic Pacific. Methods We generated a data set including mt DNA and diagnostic SNP s for 173 individuals of G. oceanica spanning Micronesia, Melanesia, and Polynesia. For a subset of these individuals, we also sequenced nuclear loci. From these data, we performed maximum likelihood and Bayesian inference to reveal major clades. We also performed Bayesian clustering analyses and coalescence–based species delimitation tests to infer the number of species in this area. Results We found evidence for six independent evolutionary lineages (candidate species) within G. oceanica that diverged between the Pliocene and the early Pleistocene, with high diversity through northern Melanesia, and pairing of northern Melanesian endemic taxa with widespread lineages across Micronesia and Polynesia. Main conclusions The islands of northern Melanesia not only have unrecognized diversity, but also were the source of independent expansions of lineages through the more remote northern and eastern Pacific. These results highlight the very different evolutionary histories of island faunas on remote archipelagos versus those across Melanesia and point to the need for more intensive studies of fauna within Melanesia if we are to understand the evolution of diversity across the tropical Pacific.

Unlocking the vault: next‐generation museum population genomics - Ke Bi; Tyler Linderoth; Dan Vanderpool; Jeffrey M. Good; Rasmus Nielsen; Craig Moritz (Molecular Ecology, 2013)
Natural history museum collections provide unique resources for understanding how species respond to environmental change, including the abrupt, anthropogenic climate change of the past century. Ideally, researchers would conduct genome‐scale screening of museum specimens to explore the evolutionary consequences of environmental changes, but to date such analyses have been severely limited by the numerous challenges of working with the highly degraded DNA typical of historic samples. Here, we circumvent these challenges by using custom, multiplexed, exon capture to enrich and sequence ~11 000 exons (~4 Mb) from early 20th‐century museum skins. We used this approach to test for changes in genomic diversity accompanying a climate‐related range retraction in the alpine chipmunks ( T amias alpinus ) in the high Sierra Nevada area of California, USA . We developed robust bioinformatic pipelines that rigorously detect and filter out base misincorporations in DNA derived from skins, most of which likely resulted from postmortem damage. Furthermore, to accommodate genotyping uncertainties associated with low‐medium coverage data, we applied a recently developed probabilistic method to call single‐nucleotide polymorphisms and estimate allele frequencies and the joint site frequency spectrum. Our results show increased genetic subdivision following range retraction, but no change in overall genetic diversity at either nonsynonymous or synonymous sites. This case study showcases the advantages of integrating emerging genomic and statistical tools in museum collection‐based population genomic applications. Such technical advances greatly enhance the value of museum collections, even where a pre‐existing reference is lacking and points to a broad range of potential applications in evolutionary and conservation biology.

The importance of an evolutionary perspective in conservation policy planning - Craig C. Moritz; Sally Potter (Molecular Ecology, 2013)
Prioritization of taxa for conservation must rest on a foundation of correctly identified species boundaries, enhanced by an understanding of evolutionary history and phylogenetic relationships. Therefore, we can incorporate both evolutionary and ecological processes into efforts to sustain biodiversity. In this issue of M olecular E cology, Malaney & Cook ( ) highlight the critical value of an evolutionary biogeographical approach, combining multilocus phylogeography with climatic niche modelling to infer phylogenetically weighted conservation priorities for evolutionary lineages of jumping mice across N orth A merica. Remarkably, they find that the P reble's meadow jumping mouse ( Z apus hudsonius preblei ), long debated as a threatened taxon, in fact represents the southern terminus of a relatively uniform lineage that expanded well into A laska during the H olocene. By contrast, some other relictual and phylogenetically divergent taxa of jumping mice likely warrant greater conservation priority. This study highlights the value of integrative approaches that place current taxonomy in a broader evolutionary context to identify taxa for conservation assessment, but also highlights the challenges in maintaining potential for adaptive responses to environmental change.

Cryptic genetic diversity in Rattus of the San Francisco Bay region, California - Chris J. Conroy; Kevin C. Rowe; Karen M. C. Rowe; Pauline L. Kamath; Ken P. Aplin; Lucia Hui; David K. James; Craig Moritz; James L. Patton (Biological Invasions, 2013)

Montane refugia predict population genetic structure in the L arge‐blotched E nsatina salamander - Thomas J. Devitt; Susan E. Cameron Devitt; Bradford D. Hollingsworth; Jimmy A. McGuire; Craig Moritz (Molecular Ecology, 2013)
Understanding the biotic consequences of P leistocene range shifts and fragmentation remains a fundamental goal in historical biogeography and evolutionary biology. Here, we combine species distribution models ( SDM ) from the present and two late Q uaternary time periods with multilocus genetic data (mitochondrial DNA and microsatellites) to evaluate the effect of climate‐induced habitat shifts on population genetic structure in the L arge‐blotched E nsatina ( E nsatina eschscholtzii klauberi ), a plethodontid salamander endemic to middle and high‐elevation conifer forest in the T ransverse and P eninsular R anges of southern C alifornia and northern B aja C alifornia. A composite SDM representing the range through time predicts two disjunct refugia, one in southern C alifornia encompassing the core of the species range and the other in the S ierra S an P edro M ártir of northern B aja C alifornia at the southern limit of the species range. Based on our spatial model, we would expect a pattern of high connectivity among populations within the northern refugium and, conversely, a pattern of isolation due to long‐term persistence of the S ierra S an P edro M ártir population. Our genetic results are consistent with these predictions based on the hypothetical refugia in that (i) historical measures of population connectivity among stable areas are correlated with gene flow estimates; and (ii) there is strong geographical structure between separate refugia. These results provide evidence for the role of recent climatic change in shaping patterns of population persistence and connectivity within the Transverse and Peninsular Ranges, an evolutionary hotspot.

The push and pull of climate change causes heterogeneous shifts in avian elevational ranges - Morgan W. Tingley; Michelle S. Koo; Craig Moritz; Andrew C. Rush; Steven R. Beissinger (Global Change Biology, 2012)
Projected effects of climate change on animal distributions primarily focus on consequences of temperature and largely ignore impacts of altered precipitation. While much evidence supports temperature‐driven range shifts, there is substantial heterogeneity in species' responses that remains poorly understood. We resampled breeding ranges of birds across three elevational transects in the S ierra N evada M ountains, USA , that were extensively surveyed in the early 20th century. Presence–absence comparisons were made at 77 sites and occupancy models were used to separate significant range shifts from artifacts of false absences. Over the past century, rising temperature pushed species upslope while increased precipitation pulled them downslope, resulting in range shifts that were heterogeneous within species and among regions. While 84% of species shifted their elevational distribution, only 51% of upper or lower range boundary shifts were upslope. By comparison, 82% of range shifts were in a direction predicted by changes in either temperature or precipitation. Species were significantly more likely to shift elevational ranges than their ecological counterparts if they had small clutch sizes, defended all‐purpose territories, and were year‐round residents, results that were in opposition to a priori predictions from dispersal‐related hypotheses. Our results illustrate the complex interplay between species‐specific and region‐specific factors that structure patterns of breeding range change over long time periods. Future projections of increasing temperature and highly variable precipitation regimes create a strong potential for heterogeneous responses by species at range margins.

Testing hypotheses for genealogical discordance in a rainforest lizard - Sonal Singhal; Craig Moritz (Molecular Ecology, 2012)
Genealogical discordance, or when different genes tell distinct stories although they evolved under a shared history, often emerges from either coalescent stochasticity or introgression. In this study, we present a strong case of mito‐nuclear genealogical discordance in the Australian rainforest lizard species complex of S aproscincus basiliscus and S . lewisi . One of the lineages that comprises this complex, the S outhern S . basiliscus lineage, is deeply divergent at the mitochondrial genome but shows markedly less divergence at the nuclear genome. By placing our results in a comparative context and reconstructing the lineages' demography via multilocus and coalescent‐based approximate B ayesian computation methods, we test hypotheses for how coalescent variance and introgression contribute to this pattern. These analyses suggest that the observed genealogical discordance likely results from introgression. Further, to generate such strong discordance, introgression probably acted in concert with other factors promoting asymmetric gene flow between the mitochondrial and nuclear genomes, such as selection or sex‐biased dispersal. This study offers a framework for testing sources of genealogical discordance and suggests that historical introgression can be an important force shaping the genetic diversity of species and their populations.

Size increase in high elevation ground squirrels over the last century - Lindsey M. Eastman; Toni Lyn Morelli; Kevin C. Rowe; Chris J. Conroy; Craig Moritz (Global Change Biology, 2012)
There is increasing evidence for morphological change in response to recent environmental change, but how this relates to fluctuations in geographic range remains unclear. We measured museum specimens from two time periods (1902–1950 and 2000–2008) that vary significantly in climate to assess if and how two high elevation contracting species of ground squirrels in the Sierra Nevada of California, Belding's ground squirrel ( Urocitellus beldingi ) and the golden‐mantled ground squirrel ( Callospermophilus lateralis ), and one lower elevation, stable species, the California ground squirrel ( Otospermophilus beecheyi ), have responded morphologically to changes over the last century. We measured skull length (condylobasal length), an ontogenetically more labile trait highly correlated with body size, and maxillary toothrow length, a more developmentally constrained trait predictive of skull shape. C. lateralis and U. beldingi , both obligate hibernators, have increased in body size, but have not changed in shape. In contrast, O. beecheyi , which only hibernates in parts of its range, has shown no significant change in either morphometric trait. The increase in body size in the higher elevation species, hypothesized to be a plastic effect due to a longer growing season and thus prolonged food availability, opposes the expected direction of selection for decreased body size under chronic warming. Our study supports that population contraction is related to physiological rather than nutritional constraints.

Palaeoclimate change drove diversification among isolated mountain refugia in the Australian arid zone - MITZY PEPPER; MATTHEW K. FUJITA; CRAIG MORITZ; J. SCOTT KEOGH (Molecular Ecology, 2011)
Refugia featured prominently in shaping evolutionary trajectories during repeated cycles of glaciation in the Quaternary, particularly in the Northern Hemisphere. The Southern Hemisphere instead experienced cycles of severe aridification but little is known about the temporal presence and role of refugia for arid‐adapted biota. Isolated mountain ranges located in the Australian arid zone likely provided refugia for many species following Mio/Pliocene ( Heteronotia that have distributions confined to major rocky ranges in the arid zone. Phylogenetic analyses show that each rocky range harbours a divergent lineage, and substantial intraspecific diversity is likely due to topographic complexity in these areas. Old divergences (∼4 Ma) among lineages pre‐date the formation of the geologically young sand deserts (

Patterns of persistence and isolation indicate resilience to climate change in montane rainforest lizards - RAYNA C. BELL; JUAN L. PARRA; MARIA TONIONE; CONRAD J. HOSKIN; JASON B. MACKENZIE; STEPHEN E. WILLIAMS; CRAIG MORITZ (Molecular Ecology, 2010)

Variable responses of skinks to a common history of rainforest fluctuation: concordance between phylogeography and palaeo‐distribution models - ADNAN MOUSSALLI; CRAIG MORITZ; STEPHEN E. WILLIAMS; ANA C. CARNAVAL (Molecular Ecology, 2009)
There is a growing appreciation of impacts of late‐Quaternary climate fluctuations on spatial patterns of species and genetic diversity. A major challenge is to understand how and why species respond individualistically to a common history of climate‐induced habitat fluctuation. Here, we combine modelling of palaeo‐distributions and mitochondrial‐DNA phylogeographies to compare spatial patterns of population persistence and isolation across three species of rainforest skinks ( Saproscincus spp.) with varying climatic preferences. Using Akaike Information Criterion model‐averaged projections, all three species are predicted to have maintained one or more small populations in the northern Wet Tropics, multiple or larger populations in the central region, and few if any in the south. For the high‐elevation species, Saproscincus czechurai , the warm–wet climate of the mid Holocene was most restrictive, whereas for the generalist S. basiliscus and lower‐elevation S. tetradactyla, the cool–dry last glacial maximum was most restrictive. As expected, S. czechurai was the most genetically structured species, although relative to modelled distributions, S. basiliscus had surprisingly deep phylogeographical structure among southern rainforest isolates, implying long‐term isolation and persistence. For both S. basiliscus and S. tetradactyla, there was high genetic diversity and complex phylogeographical patterns in the central Wet Tropics, reflecting persistence of large, structured populations. A previously identified vicariant barrier separating northern and central regions is supported, and results from these species also emphasize a historical persistence of populations south of another biogeographical break, the Tully Gorge. Overall, the results support the contention that in a topographically heterogeneous landscape, species with broader climatic niches may maintain higher and more structured genetic diversity due to persistence through varying climates.

Historical climate modelling predicts patterns of current biodiversity in the Brazilian Atlantic forest - Ana Carolina Carnaval; Craig Moritz (Journal of Biogeography, 2008)
Aim We aim to propose validated, spatially explicit hypotheses for the late Quaternary distribution of the Brazilian Atlantic forest, and thereby provide a framework for integrating analyses of species and genetic diversity in the region. Location The Atlantic forest, stretching along the Brazilian coast. Methods We model the spatial range of the forest under three climatic scenarios (current climate, 6000 and 21,000 years ago) with BIOCLIM and MAXENT. Historically stable areas or refugia are identified as the set of grid cells for which forest presence is inferred in all models and time projections. To validate inferred refugia, we test whether our models are matched by the current distribution of the forest and by fossil pollen data. We then investigate whether the location of inferred forest refugia is consistent with current patterns of species endemism and existing phylogeographical data. Results Forest models agree with pollen records and predict a large area of historical forest stability in the central corridor (Bahia), as well as a smaller refuge (Pernambuco) along the Brazilian coast, matching current centres of endemism in multiple taxa and mtDNA diversity patterns in a subset of the species examined. Less historical stability is predicted in coastal areas south of the Doce river, which agrees with most phylogeographical studies in that region. Yet some widely distributed taxa show high endemism in the southern Atlantic forest. This may be due to limitations of the modelling approach, differences in ecology and dispersal capability, historical processes not contemplated by the current study or inadequacy of the available test data sets. Main conclusions Palaeoclimatic models predict the presence of historical forest refugia in the Atlantic rain forest and suggest spatial variation in persistence of forests through the Pleistocene, predicting patterns of biodiversity in several local taxa. The results point to the need for further studies to document genetic and species endemism in the relatively poorly known and highly impacted areas of Atlantic rain forests of north‐eastern Brazil.

The California Hotspots Project: identifying regions of rapid diversification of mammals - EDWARD BYRD DAVIS; MICHELLE S. KOO; CHRIS CONROY; JAMES L. PATTON; CRAIG MORITZ (Molecular Ecology, 2008)
The high rate of anthropogenic impact on natural systems mandates protection of the evolutionary processes that generate and sustain biological diversity. Environmental drivers of diversification include spatial heterogeneity of abiotic and biotic agents of divergent selection, features that suppress gene flow, and climatic or geological processes that open new niche space. To explore how well such proxies perform as surrogates for conservation planning, we need first to map areas with rapid diversification —‘evolutionary hotspots’. Here we combine estimates of range size and divergence time to map spatial patterns of neo‐endemism for mammals of California, a global biodiversity hotspot. Neo‐endemism is explored at two scales: (i) endemic species, weighted by the inverse of range size and mtDNA sequence divergence from sisters; and (ii) as a surrogate for spatial patterns of phenotypic divergence, endemic subspecies, again using inverse‐weighting of range size. The species‐level analysis revealed foci of narrowly endemic, young taxa in the central Sierra Nevada, northern and central coast, and Tehachapi and Peninsular Ranges. The subspecies endemism‐richness analysis supported the last four areas as hotspots for diversification, but also highlighted additional coastal areas (Monterey to north of San Francisco Bay) and the Inyo Valley to the east. We suggest these hotspots reflect the major processes shaping mammal neo‐endemism: steep environmental gradients, biotic admixture areas, and areas with recent geological/climate change. Anthropogenic changes to both environment and land use will have direct impacts on regions of rapid divergence. However, despite widespread changes to land cover in California, the majority of the hotspots identified here occur in areas with relatively intact ecological landscapes. The geographical scope of conserving evolutionary process is beyond the scale of any single agency or nongovernmental organization. Choosing which land to closely protect and/or purchase will always require close coordination between agencies.

Comparative phylogeography and speciation of dung beetles from the Australian Wet Tropics rainforest - KAREN L. BELL; CRAIG MORITZ; ADNAN MOUSSALLI; DAVID K. YEATES (Molecular Ecology, 2007)
In tropical rainforests, insects show especially high species richness and local endemism of species relative to vertebrates. One possible cause is that insects respond to historical fluctuations of rainforests on a smaller spatial scale than do vertebrates. To evaluate this hypothesis, we combine environmental niche models and mitochondrial DNA phylogeography for two pairs of sister species of the dung beetle genus Temnoplectron ( T. aeneopiceum – T. subvolitans and T. politulum – T. reyi ) from the rainforests of northeastern Australia, where climate‐driven rainforest fluctuations in the Quaternary have strongly influenced genetic and species diversity of vertebrates. Within both species pairs, the bioclimatic niche was conserved, but the T. aeneopiceum – T. subvolitans species pair had the narrower environmental range, and thus more restricted potential distribution. Coalescent analyses indicated Late Pliocene or Early Pleistocene divergences for both species pairs, and earlier speciation in ( T. aeneopiceum – T. subvolitans ) than in ( T. politulum – T. reyi ). Phylogeographic structure in ( T. aeneopiceum – T. subvolitans ) was more pronounced than in ( T. politulum – T. reyi ), with significant isolation‐by‐distance in the former species‐pair only. Nested clade and coalescence analyses indicated local range expansions for the T. aeneopiceum – subvolitans species pair and range‐wide expansion for both T. politulum and T. reyi . We suggest that stronger phylogeographic structure and earlier divergence in ( T. aeneopiceum – T. subvolitans ) than in ( T. politulum–T. reyi ) reflects a stronger influence of environmental barriers to gene flow under the present climate and greater sensitivity to warmer and drier periods of the Quaternary. The two species pairs evidently responded to Quaternary rainforest fluctuations at spatial scales similar to those seen within low‐vagility species of vertebrate. Despite this similarity of scale, these insect lineages are reproductively isolated at parapatric boundaries, whereas analogous lineages of vertebrates often are not. We suggest that rapid evolution of genitalia may facilitate geographic speciation in rainforest beetles.

The genetic structure of Australasian green turtles ( Chelonia mydas ): exploring the geographical scale of genetic exchange - KIKI E. M. DETHMERS; DAMIEN BRODERICK; CRAIG MORITZ; NANCY N. FITZSIMMONS; COLIN J. LIMPUS; SHANE LAVERY; SCOTT WHITING; MICK GUINEA; ROBERT I. T. PRINCE; ROD KENNETT (Molecular Ecology, 2006)
Ecological and genetic studies of marine turtles generally support the hypothesis of natal homing, but leave open the question of the geographical scale of genetic exchange and the capacity of turtles to shift breeding sites. Here we combine analyses of mitochondrial DNA (mtDNA) variation and recapture data to assess the geographical scale of individual breeding populations and the distribution of such populations through Australasia. We conducted multiscale assessments of mtDNA variation among 714 samples from 27 green turtle rookeries and of adult female dispersal among nesting sites in eastern Australia. Many of these rookeries are on shelves that were flooded by rising sea levels less than 10 000 years ( c . 450 generations) ago. Analyses of sequence variation among the mtDNA control region revealed 25 haplotypes, and their frequency distributions indicated 17 genetically distinct breeding stocks (Management Units) consisting either of individual rookeries or groups of rookeries in general that are separated by more than 500 km. The population structure inferred from mtDNA was consistent with the scale of movements observed in long‐term mark–recapture studies of east Australian rookeries. Phylogenetic analysis of the haplotypes revealed five clades with significant partitioning of sequence diversity (Φ = 68.4) between Pacific Ocean and Southeast Asian/Indian Ocean rookeries. Isolation by distance was indicated for rookeries separated by up to 2000 km but explained only 12% of the genetic structure. The emerging general picture is one of dynamic population structure influenced by the capacity of females to relocate among proximal breeding sites, although this may be conditional on large population sizes as existed historically across this region.

Climate change and the origin of migratory pathways in the Swainson's thrush, Catharus ustulatus - Kristen C. Ruegg; Robert J. Hijmans; Craig Moritz (Journal of Biogeography, 2006)
Aim To provide a spatially explicit model of how geographic distributions at the last glacial maximum (LGM) and post‐glacial colonization routes shaped current migratory pathways in the Swainson's thrush, Catharus ustulatus , a long‐distance migratory bird. Location The Swainson's thrush breeds in boreal forest regions of the United States and Canada as well as in riparian woodlands along the Pacific coast of North America. Methods Palaeodistribution modelling is combined with mtDNA phylogeography to predict the breeding range of the Swainson's thrush at the LGM. Quantitative environmental analysis and bioclimatic modelling are used to reconstruct the most likely post‐glacial colonization pathways. A maximum likelihood method for estimating growth rates is used to approximate the relative change in population size since the LGM. Main conclusions The palaeodistribution models are concordant with the Swainson's thrush mtDNA phylogeography, suggesting that the inland and coastal groups were geographically isolated in eastern (inland) and western (coastal) regions at the LGM. Estimates of change in population size based on genetic data are remarkably consistent with estimates of change in range size, suggesting that the coastal group has undergone a 2‐ to 3‐fold demographic and range expansion, while the inland group has undergone a 6‐ to 12‐fold demographic and range expansion since the LGM. Bioclimatic analyses strongly support the hypothesis that populations expanding out of the east into previously glaciated areas in the west were undergoing a natural extension of their range by tracking the changes in climatic conditions. The combination of bioclimatic and molecular analyses is consistent with the idea that coastal and inland groups expanded from separate eastern and western regions after the LGM and that the current migratory pathway of the inland group retraces its post‐glacial colonization route.

FAST‐TRACK: Waves of parthenogenesis in the desert: evidence for the parallel loss of sex in a grasshopper and a gecko from Australia - MICHAEL KEARNEY; MARK J. BLACKET; JARED L. STRASBURG; CRAIG MORITZ (Molecular Ecology, 2006)
The rarity of parthenogenesis, reproduction without sex, is a major evolutionary puzzle. To understand why sexual genetic systems are so successful in nature, we must understand why parthenogenesis sometimes evolves and persists. Here we use DNA sequence data to test for similarities in the tempo and mode of the evolution of parthenogenesis in a grasshopper and a lizard from the Australian desert. We find spectacular congruence between genetic and geographic patterns of parthenogenesis in these distantly related organisms. In each species, parthenogenesis evolved twice and appears to have expanded in parallel waves across the desert, suggesting a highly general selective force against sex.

Genetic diversity and population structure of Tasmanian devils, the largest marsupial carnivore - MENNA E. JONES; DAVID PAETKAU; ELI GEFFEN; CRAIG MORITZ (Molecular Ecology, 2004)
Genetic diversity and population structure were investigated across the core range of Tasmanian devils ( Sarcophilus laniarius ; Dasyuridae), a wide‐ranging marsupial carnivore restricted to the island of Tasmania. Heterozygosity (0.386–0.467) and allelic diversity (2.7–3.3) were low in all subpopulations and allelic size ranges were small and almost continuous, consistent with a founder effect. Island effects and repeated periods of low population density may also have contributed to the low variation. Within continuous habitat, gene flow appears extensive up to 50 km (high assignment rates to source or close neighbour populations; nonsignificant values of pairwise F ST ), in agreement with movement data. At larger scales (150–250 km), gene flow is reduced (significant pairwise F ST ) but there is no evidence for isolation by distance. The most substantial genetic structuring was observed for comparisons spanning unsuitable habitat, implying limited dispersal of devils between the well‐connected, eastern populations and a smaller northwestern population. The genetic distinctiveness of the northwestern population was reflected in all analyses: unique alleles; multivariate analyses of gene frequency (multidimensional scaling, minimum spanning tree, nearest neighbour); high self‐assignment (95%); two distinct populations for Tasmania were detected in isolation by distance and in Bayesian model‐based clustering analyses. Marsupial carnivores appear to have stronger population subdivisions than their placental counterparts.

Limited effect of anthropogenic habitat fragmentation on molecular diversity in a rain forest skink, Gnypetoscincus queenslandiae - Joanna Sumner; Tim Jessop; David Paetkau; Craig Moritz (Molecular Ecology, 2004)
To examine the effects of recent habitat fragmentation, we assayed genetic diversity in a rain forest endemic lizard, the prickly forest skink ( Gnypetoscincus queenslandiae ), from seven forest fragments and five sites in continuous forest on the Atherton tableland of northeastern Queensland, Australia. The rain forest in this region was fragmented by logging and clearing for dairy farms in the early 1900s and most forest fragments studied have been isolated for 50–80 years or nine to 12 skink generations. We genotyped 411 individuals at nine microsatellite DNA loci and found fewer alleles per locus in prickly forest skinks from small rain forest fragments and a lower ratio of allele number to allele size range in forest fragments than in continuous forest, indicative of a decrease in effective population size. In contrast, and as expected for populations with small neighbourhood sizes, neither heterozygosity nor variance in allele size differed between fragments and sites in continuous forests. Considering measures of among population differentiation, there was no increase in F ST among fragments and a significant isolation by distance pattern was identified across all 12 sites. However, the relationship between genetic ( F ST ) and geographical distance was significantly stronger for continuous forest sites than for fragments, consistent with disruption of gene flow among the latter. The observed changes in genetic diversity within and among populations are small, but in the direction predicted by the theory of genetic erosion in recently fragmented populations. The results also illustrate the inherent difficulty in detecting genetic consequences of recent habitat fragmentation, even in genetically variable species, and especially when effective population size and dispersal rates are low.

Absence of evidence for isolation by distance in an expanding cane toad ( Bufo marinus ) population: an individual‐based analysis of microsatellite genotypes - Raphael Leblois; François Rousset; Dani Tikel; Craig Moritz; Arnaud Estoup (Molecular Ecology, 2000)
The cane toad ( Bufo marinus ) was introduced in 1935 in Australia, where it spread rapidly. We have tested for isolation by distance by analysing at a local geographical scale a continuous population using seven microsatellite markers and an individual‐based method. The matrix of pairwise individual differentiation was not significantly correlated with that of geographical distance. Regression analyses gave a low positive slope of 0.00072 (all individuals) or a negative slope of 0.0017 (individuals with a distance higher than the previously estimated mean dispersal distance). The absence of evidence for isolation by distance favours the hypothesis that the substantial differentiation and autocorrelation previously observed at enzyme loci, mainly results from discontinuities in the colonization process with founder effects occurring at the time of the establishment of new populations.

Comparative phylogeography and the identification of genetically divergent areas for conservation - CRAIG MORITZ; DANIEL P. FAITH (Molecular Ecology, 1998)
Genetic diversity is recognized as a fundamental component of biodiversity and its protection is incorporated in several conventions and policies. However, neither the concepts nor the methods for assessing conservation value of the spatial distribution of genetic diversity have been resolved. Comparative phylogeography can identify suites of species that have a common history of vicariance. In this study we explore the strengths and limitations of Faith’s measure of ‘Phylogenetic Diversity’ (PD) as a method for predicting from multiple intraspecific phylogeographies the underlying feature diversity represented by combinations of areas. An advantage of the PD approach is that information on the spatial distribution of genetic diversity can be combined across species and expressed in a form that allows direct comparison with patterns of species distributions. It also seeks to estimate the same parameter, feature diversity, regardless of the level of biological organization. We extend the PD approach by using Venn diagrams to identify the components of PD, including those unique to or shared among areas and those which represent homoplasy on an area tree or which are shared across all areas. PD estimation should be complemented by analysis of these components and inspection of the contributing phylogeographies. We illustrate the application of the approach using mtDNA phylogeographies from vertebrates resident in the wet tropical rainforests of north‐east Queensland and compare the results to biodiversity assessments based on the distribution of endemic vertebrate species. The genetic vs. species approaches produce different assessments of conservation value, perhaps reflecting differences in the temporal and spatial scale of the determining processes. The two approaches should be seen as complementary and, in this case, conservation planning should incorporate information on both dimensions of biodiversity.

Evolutionary Distinctiveness and Status of the Endangered Lake Eacham Rainbowfish (Melanotaenia eachamensis) - Danqing Zhu; Sandie Degnan; Craig Moritz (Conservation Biology, 1998)

Evolutionary Distinctiveness and Status of the Endangered Lake Eacham Rainbowfish ( Melanotaenia eachamensis ) - Danqing Zhu; Sandie Degnan; Craig Moritz (Conservation Biology, 1998)
The Lake Eacham rainbowfish (Melanotaenia eachamensis) was declared extinct in the wild in the late 1980s after it disappeared from its only known locality, an isolated crater lake in northeast Queensland. Doubts have been raised about whether this taxon is distinct from surrounding populations of the eastern rainbowfish (Melanotaenia splendida splendida). We examined the evolutionary distinctiveness of M. eachamensis, obtained from captive stocks, relative to M. s. splendida through analysis of variation in mtDNA sequences, nuclear microsatellites, and morphometric characters. Captive M. eachamensis had mtDNAs that were highly divergent from those in most populations of M. s. splendida. A broader geographic survey using RFLPs revealed some populations, initially identified as M. s. splendida, that carried eachamensis mtDNA, whereas some others had mixtures of eachamensis and splendida mtDNA. The presence of eachamensis‐like mtDNA in these populations could in principle be due to (1) sorting of ancestral polymorphisms, (2) introgression of M. eachamensis mtDNA into M. s. splendida, or (3) incorrect species boundaries, such that some populations currently assigned to M. s. splendida are M. eachamensis or are mixtures of the two species. These alternative hypotheses were evaluated through comparisons of four nuclear microsatellite loci and morphometrics and meristics. In analyses of both data sets, populations of M. s. splendida with eachamensis mtDNA were more similar to captive M. eachamensis than to M. s. splendida with splendida mtDNA, supporting hypothesis 3. These results are significant for the management of M. eachamensis in several respects. First, the combined molecular and morphological evidence indicates that M. eachamensis is a distinct species and a discrete evolutionarily significant unit worthy of conservation effort. Second, it appears that the species boundary between M. eachamensis and M. s. splendida has been misdiagnosed, such that there are extant populations on the Atherton Tableland as well as areas where both forms coexist. Accordingly, we suggest that M. eachamensis be listed as vulnerable, rather than critical (or extinct in the wild). Third, the discovery of extant but genetically divergent populations of M. eachamensis on the Atherton Tableland broadens the options for future reintroductions to Lake Eacham. Distintividad Evolutiva y Estatus del Amenazado Pez Arcoíris ( Melanotaenia eachamensis ) del lago Eacham El pez acoíris del lago Eacham (Melanotaenia eachamensis) fue declarado extinto de poblaciones silvestres a finales de los 80’s después de su desaparición de la única localidad conocida, un cráter aislado en el noreste de Queensland. Se han incrementado las dudas acerca de si este taxón es distinto de las poblaciones circunvecinas del pez arcoiris del este (Melanotaenia spendida splendida). Examinamos la difernciación evolutiva de M. eachamensis, obtenida de stocks cautivos, en relación con M. s. splendida mediante un análisis de variación en secuencias de ADNmt, nuclear, microsatélites y caracteres morfométricos. M. eachamensis cautivos tuvieron ADNmt que difirió grandemente de aquellos provenientes de la mayoría de las poblaciones de M. s. splendida. Un estudio geográfico mas amplio usando RFLPs reveló que algunas poblaciones inicialmente identificados como M. s. splendida, contenían ADNmt de eachamensis, mientras que otros presentaron mezclas de DNAmt de eachamensis y splendida. La presencia de DNAmt del tipo de eachamensis en estas poblaciones, podría en principio, deberse a 1) una forma de polimorfismos ancestrales, 2) Introgresión del ADNmt de M. eachamensis hacia M. s. splendida o 3) límites incorrectos para las especies, tal como que algunas poblaciones actualmente asignadas al ADNmt de M. s. splendida son M. eachamensis o son una mezcla de las dos especies. Estas hipótesis alternativas fueron evaluadas mediante comparaciones de cuatro loci microsatélites nucleares y datos morfométricos y merísticos. En el análisis de ambas bases de datos, las poblaciones de M. s. splendida con DNAmt de M. eachamensis fueron mas similares a M. eachamensis cautivos que a M. s. splendida con ADNmt de splendida, esto soporta la hipótesis 3. Estos resultados son significativos para el manejo de M. eachamensis en diversos aspectos. Primero, las evidencias moleculares y morfológicas indican que M. eachamensis es una especie distintiva y una unidad evolutiva significante, lo suficientemente valiosa como para un esfuerzo conservacionista. Segundo, si parece que los limites de especies entre M. eachamensis y M. s. splendida han sido mal diagnosticados, a tal grado que hay poblaciones existentes en el altiplano de Atherton, asi como en áreas donde ambas formas coexisten. De acuerdo con esto, sugerimos que M. eachamensis debe ser enlistada como vulnerable, en lugar de crítica (o extinta). Tercero, el descubrimiento de poblaciones existentes, pero genéricamente divergentes de M. eachamensis en el altiplano de Atherton amplía las opciones para futuras reintroducciones en el lago Eacham. X775047

Versatile primers for the amplification of the mitochondrial DNA control region in marsupials - Luca Fumagalli; Lisa C. Pope; Pierre Taberlet; Craig Moritz (Molecular Ecology, 1997)

Cryptic diversity in an endemic rainforest skink (Gnypetoscincus queenslandiae) - Craig Moritz; Leo Joseph; Mark Adams (Biodiversity and Conservation, 1993)